Analisis Situasi Didaktis pada Modul Ajar Penjumlahan dan Pengurangan Bilangan Cacah Kelas 2 Sekolah Dasar - Syarifah, Mufarrahatus; Bramantha, Heldie (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2025)
This research aims to describe how students’ understanding of adding and subtracting whole numbers is formed. This research is a qualitative descriptive study with teaching modules as the main data source. After surveying didactic situation theory in mathematics through various sources, the paradigm in this theory is then used as a basis for describing learning activities contained in the teaching module. Learning activities in the teaching module are classified based on the theory of mathematical didactic situations. The result shows that in these learning activities, the didactical situation was not developed sequentially. Apart from that, the action situation that is constructed does not show the existence of a dialectical situation between individual students and the milieu. Knowledge construction tends to come from teacher explanations, not from the process of solving problems that involve students' mental activity. This condition can potentially cause knowledge not to be constructed properly, making it possible for students not to be able to use it when facing new mathematical problems and allowing learning obstacles to occur. Keywords: didactical situations, teaching module